Pelatihan Seni Tradisi Tari Likok Pulo untuk Siswa Laki-Laki sebagai Upaya Meningkatkan Minat dan Pelestarian Budaya Aceh di SMPN 1 Darul Imarah - Cut Zuriana; Yeni Zuryaningsih (Jurnal Kemitraan Masyarakat, 2025)
This community service activity aims to increase the motivation, confidence, and love of male students for traditional Acehnese art, particularly the Likok Pulo dance. This dance is characterized by its energetic and rhythmic nature, making it suitable as a dance teaching material for male students who have previously shown little interest in participating in dance activities. The methods used include demonstrations and peer tutoring, covering training in various dance movements, mastering the lyrics, and accompanying music with the rapa’i instrument. The training was conducted over three days from 2:00 PM to 5:00 PM. The dancers involved were specifically male students who had previously shown little interest in dance practice. The results of the activity showed that male students were highly enthusiastic, as evidenced by their ability to master movement variations, sing lyrics, and play musical accompaniment in a short period of time, despite having never participated in dance extracurricular activities before. This activity demonstrated that selecting appropriate dance material can change students' negative perceptions of dance and serve as a medium for preserving local culture through formal education.